Collective improvisation in emergency response. (March 2021) - Roud, Ensieh
Highlights: Pinpointed that collective improvisation in Arctic Sea emergencies is critical. Explored the relationship between joint training and collective improvisation. Proposed a conceptual model that should be tested both qualitatively and quantitative. Contributed to the organizational and inter-organizational aspect of emergency response. Abstract: Emergencies are characterized by ambiguity and high stress. An emergency response typically involves a blend of public, private, and volunteer organizations. Responding to emergencies requires the capability to face unforeseen incidents and adequately adapt to them. The need for improvisation can be imperative for the success of an operation. Moreover, the interconnected nature of emergencies mandates collaboration, and collective improvisation can be a tool for handling challenges under the extreme complexity of an emergency. In this study, joint training is linked to the capability of collective improvisation in emergency response at an interorganizational level. The aim of this semi-conceptual study is to explore how joint training can improve collective improvisation capability in emergency response. To meet this aim, a literature review and pilot study are conducted. The context of this study is the management of emergency response in the Norwegian Arctic Sea region. The Arctic Sea region has a harsh climate with limited resources where involved organizations include both civil and military organizations, which makes the improvisation even more critical. This study shows that organizational memory, interorganizational trust, interorganizational communication, and information sharing are prerequisites and mediating variables that positively influence collective improvisation. Organizational structure and complex context also influence collective improvisation in emergency response.